Editorial note - Davids, M Razeen (African Journal of Nephrology, 2017)
Now that we have successfully migrated to our new online platform, AJN has taken the additional step of adopting a “publish-as-you-go” strategy. Articles will be published once they have been accepted and there will no longer be the usual wait until the next issue is published. New articles will be added throughout the year and will therefore be available to be read and cited much sooner. The latest articles which we are now publishing include a short review by Halperin on the assessment of the renal response in patients with potassium disorders. Halperin first gave us the well-known transtubular K+ gradient (TTKG) but in recent years has been recommending the use of the urine K+/creatinine ratio instead. In this article he explains the reasons for this change. Kapembwa et al. present their data on technique survival in patients on peritoneal dialysis (PD) at Tygerberg Hospital in Cape Town. Successfully maintaining patients on PD is especially important when a PD-first policy is being followed, as is the case at their centre. The issue of the access of rural patients with chronic kidney disease to healthcare is the topic of the paper by Singh et al., who report on referral patterns at a tertiary centre in Durban, South Africa. The paper by Camara et al., from the Free State province, South Africa, describes the outcomes of patients with acute kidney injury who needed continuous renal replacement therapy. In their cohort, patients with HIV infection were substantially younger and had a much worse outcome. Finally, the report by Makhoba et al. describes a case of osseous metaplasia in a renal allograft. M Razeen Davids Associate Editor